Systemy zarządzania przepływem pracy - Cichoń, Dariusz; Sala, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The conception of workflow management ensuring the correct circulation of documents in an enterprise is being substituted by the more difficult task - business processes flow in the whole enterprise. This demands introducing of innovative solutions in the areas of communication, сo-creating and using of documents, and control of the business processes. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 60-67